Developing Anti Domestic Violence Policy during Covid 19 Pandemic in Indonesia - Purwanti, Ani; Setiawan, Fajar Ahmad (Faculty of Law, Universitas Brawijaya, 2020)
COVID-19 (a new strain of corona virus) has been declared a global pandemic. In Indonesia, The measures announced over the past few months have drastically changed people's daily lives. However, there are negative, unintended consequences. As the virus continues to spread around the world, it brings many new stresses, including physical and psychological health risks, isolation and loneliness, the closure of many schools and businesses, economic vulnerability, and job loss. Through all of this, children and their mothers are very vulnerable (End Violence against Children, 2020) to the risk of domestic violence. Currently, Covid-19 is a serious threat to the human population on earth because even though it has a health security dimension, it has an impact on other security dimensions. This research concluded that the domestic violence, in gender mainstreamed legal studies, can be included as a threat to human security (human security) which is exacerbated by the pandemic. In the context of policy, Covid-19 requires the participation of various national and cross-country actors, countries and state actors in efforts to resolve it. In that category, the state needs to work with various non-state actors to eradicate domestic violence.